Noncommunicable disease risk factors and predictors of hypertension among Gurkha veterans in Nepal: a community-based cross-sectional study - Nilam Adhikari; Krishna Prasad Sapkota; Sagar Panthi; Rochana Acharya; Madhav Bhusal; Sangita Bhattarai; Gampo Dorji; Shyam Sundar Budhathoki; Dharanidhar Baral; Paras K. Pokharel (BMC Public Health)
Abstract Background Nepal faces a rising burden of noncommunicable diseases (NCDs), yet Gurkha veterans—a population with distinct sociocultural backgrounds, occupational exposures, and post-service lifestyle transitions;remain largely overlooked in NCD research. Their increased susceptibility to sedentary behavior and unhealthy dietary habits may contribute to heightened NCD risks. This study assesses key behavioral (smoking, alcohol use, diet, and physical inactivity) and metabolic (obesity, elevated blood pressure) risk factors and identifies predictors of hypertension among Gurkha veterans. Methods A community-based cross-sectional study was conducted in Palpa district, Lumbini Province, Nepal, in 2019. A multistage sampling technique was employed to determine the sample size, and a total of 189 Gurkha veterans were interviewed for data collection. Data were analyzed using SAS software (Version 9.4). A Bivariate analysis was conducted to assess the statistical associations among NCD risk factors, followed by multivariable logistic regression to identify independent predictors of hypertension while controlling for potential confounders. Results The study revealed a high prevalence of daily alcohol consumption (41.80%), and inadequate fruit intake (89.95%. Likewise, 28.57% of the Gurkha veterans had lower intake of vegetables and 26.98% of them were performing low physical activity of vigorous level. Moreover, 35.98% had overweight and obesity and, nearly half of the participants (47.62%) were hypertensive. Multivariable logistic regression showed that daily alcohol drinkers (AOR: 3.13, 95% CI: 1.56–6.25, p=0.001), those engaging in less than 75 minutes per week of vigorous physical activity (AOR: 4.82, 95% CI: 1.89–12.30, p=0.001), and those with overweight or obese status (AOR: 3.50, 95% CI: 1.70–7.22, p<0.001) had significantly higher odds of having hypertension. Conclusion Alcohol consumption, physical inactivity, and obesity were the strongest predictors of hypertension among ex-Gurkha soldiers. Given the distinct lifestyle transitions and health challenges faced by this population, targeted early screening, at the community level with a continuum of care and health promotion strategies are essential to mitigate the NCD burden among retired Gurkha soldiers.